Eriodictyol ameliorates cognitive dysfunction in APP/PS1 mice by inhibiting ferroptosis via vitamin D receptor-mediated Nrf2 activation - Lin Li; Wen-Jun Li; Xiang-Ru Zheng; Qing-Long Liu; Qian Du; Yu-Jie Lai; Song-Qing Liu (BMC, 2022)
Abstract Background Alzheimer's disease (AD) is the most common type of neurodegenerative disease in the contemporary era, and it is still clinically incurable. Eriodictyol, a natural flavonoid compound that is mainly present in citrus fruits and some Chinese herbal medicines, has been reported to exert anti-inflammatory, antioxidant, anticancer and neuroprotective effects. However, few studies have examined the anti-AD effect and molecular mechanism of eriodictyol. Methods APP/PS1 mice were treated with eriodictyol and the cognitive function of mice was assessed using behavioral tests. The level of amyloid-β (Aβ) aggregation and hyperphosphorylation of Tau in the mouse brain were detected by preforming a histological analysis and Western blotting. HT-22 cells induced by amyloid-β peptide (1-42) (Aβ1-42) oligomers were treated with eriodictyol, after which cell viability was determined and the production of p-Tau was tested using Western blotting. Then, the characteristics of ferroptosis, including iron aggregation, lipid peroxidation and the expression of glutathione peroxidase type 4 (GPX4), were determined both in vivo and in vitro using Fe straining, Western blotting and qPCR assays. Additionally, the expression level of vitamin D receptor (VDR) and the nuclear factor erythroid 2-related factor 2/heme oxygenase-1 (Nrf2/HO-1) signaling pathway were tested using Western blotting and qPCR assays. Afterward, HT-22 cells with VDR knockout were used to explore the potential mechanisms, and the relationship between VDR and Nrf2 was further assessed by performing a coimmunoprecipitation assay and bioinformatics analysis. Results Eriodictyol obviously ameliorated cognitive deficits in APP/PS1 mice, and suppressed Aβ aggregation and Tau phosphorylation in the brains of APP/PS1 mice. Moreover, eriodictyol inhibited Tau hyperphosphorylation and neurotoxicity in HT-22 cells induced by Aβ1-42 oligomer. Furthermore, eriodictyol exerted an antiferroptosis effect both in vivo and in vitro, and its mechanism may be associated with the activation of the Nrf2/HO-1 signaling pathway. Additionally, further experiments explained that the activation of Nrf2/HO-1 signaling pathway by eriodictyol treatment mediated by VDR. Conclusions Eriodictyol alleviated memory impairment and AD-like pathological changes by activating the Nrf2/HO-1 signaling pathway through a mechanism mediated by VDR, which provides a new possibility for the treatment of AD.